Chylous ascites: Our experience from a resource-limited setting. (January 2023) - Suleman, Mujaheed; Mohamedali, Abbas; Sadiq, Adnan; Tendai, Joylene; Lodhia, Jay
Abstract: Introduction and importance: Chyle is a lipid-rich, milky-appearing fluid originating from lymph tissues. Chylous ascites is the collection of chyle in the peritoneal cavity and is a rare pathology. Case presentation: In this case report we share our experience of successfully managing chylous ascites conservatively from a resource-limited setting. Clinical discussion: There are numerous causes hence management includes treating the cause. Generally responds well to conservative management however some cases require surgical intervention. Conclusion: Ascitic tapping is an effective diagnostic and therapeutic tool is chylous ascites. Highlights: Chylous ascites is a rare pathology accounting in less than 1 %. Clinicians should thrive to establish the cause for management plan. Chylous ascites responds well to conservative management. Abdominal drain is an effective diagnostic and management tool.